(untitled) (Świat Idei i Polityki, 2006)
Mind sobriety and good physical condition contribute to taking accurate and proper decisions by politicians. However, it often happens that political decision-makers do not obey some rules. They pursue political power at all cost, regardless of their health condition. This not only influences them badly but also affects their social decisions. It is often impossible to verify and put off ill politicians, because they providently suppress their trouble. An illness is to a large extent defined as a factor deforming the intentions of political decision-makers. Affected by a strong pain, a politician can make far-reaching concessions only to rest. It is claimed that the older you are the more experience you have to rule. But you also acquire illnesses that should be balanced by experience. It happens that health trouble takes priority in a critical situation. Not without a reason does the author combine the age factor and a pathogen, as the text concerns Ronald Reagan who while taking his presidential office in the White House was almost seventy.